2014
DOI: 10.1080/1064119x.2013.815673
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Size in Occurrence, Distribution, Morphological Characteristics, Abundance, and Resource Evaluation of Polymetallic Nodules

Abstract: About 13000 different sized nodules from 249 locations covering 75000 km 2 relinquished Pioneer area in the Central Indian Basin (CIB) have been studied by assorting them in groups of 1 cm size intervals. The study shows systematic variation, and inverse relationship of nodule size with the occurrence, distribution, grade, abundance, and Mn/Fe ratios. The study indicates that only 3-4 cm sized nodules in the first generation mine (FGM) site area are resourceful and have highest economical potential. The differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The first step in mining and utilising deep-sea minerals, particularly ferromanganese deposits (nodules and/ or crusts), is the development of an efficient method that can explore vast areas during reconnaissance exploration to find unknown distribution of the resources and narrow down the high potential region(s). A large number of primary explorations since the 1970s that used a freefall grab, box corer, deep-tow photography system or submersible dive (or a combination of these approaches) revealed that the distribution density of ferromanganese nodules fluctuates over various spatial scales in response to a changing topography and the thickness of the associated pelagic sediment (Cochonat et al 1992;Craig 1979;Piper and Blueford 1982;Sharma and Kodagali 1993;Sharma, Khadge, and Jai Sankar 2013;Usui et al 1987;Valsangkar and Rebello 2015). However, a critical problem in using such equipment (except for submersible observation) is the requirement of extensive effort when analysing vast areas, owing to a low spatial resolution and requirement of quite large number of data points (sampling points).…”
Section: Introductionmentioning
confidence: 99%
“…The first step in mining and utilising deep-sea minerals, particularly ferromanganese deposits (nodules and/ or crusts), is the development of an efficient method that can explore vast areas during reconnaissance exploration to find unknown distribution of the resources and narrow down the high potential region(s). A large number of primary explorations since the 1970s that used a freefall grab, box corer, deep-tow photography system or submersible dive (or a combination of these approaches) revealed that the distribution density of ferromanganese nodules fluctuates over various spatial scales in response to a changing topography and the thickness of the associated pelagic sediment (Cochonat et al 1992;Craig 1979;Piper and Blueford 1982;Sharma and Kodagali 1993;Sharma, Khadge, and Jai Sankar 2013;Usui et al 1987;Valsangkar and Rebello 2015). However, a critical problem in using such equipment (except for submersible observation) is the requirement of extensive effort when analysing vast areas, owing to a low spatial resolution and requirement of quite large number of data points (sampling points).…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of nodules reflects the conditions of their formation (BATURIN, 1988 Morphological studies relying on a high number of samples have been performed (VINEESH et al, 2009;MAYUMY AMPARO et al, 2013;VALSANGKAR;REBELLO, 2015). Nevertheless, none of them considered in detail the internal structure of the nodules.…”
Section: Introductionmentioning
confidence: 99%